Role of GA3 Application and Time of Sowing on Seed Germination of Hypericum perforatum Linn. - Singh, Joginder; Raina, R.; Rajasekaran, A. (Indian Forester, 2008)
Hypericum perfortaum L. (Family: Hypericaceae), commonly known as "St. John’s Wort" is an important medicinal plant valued for its anti-depressant activity. In the present work role of GA3 application and time of seed sowing on seed germination of Indian populations of Hypericum perforatum growing in Himachal Pradesh was studied. Seeds were sown on four different dates viz D1 (February 13), D2 (March 1), D3 (March 15) and D4 (April 1) and treated with different concentration of GA3 solution. The results showed that seeds sown on 15th March (D3) gave the maximum germination of 57.15 per cent, shortest peak germination period of 21.55 days (D3), the earliest germination initiation of 14.4 days and the shortest seed germination period of 33.55 days (D3). Seeds treated with 150 ppm GA3 (T4) gave the highest seed germination percentage (45.63), which is significantly higher than 29.19 per cent seed germination in untreated seeds. The results suggested that time of sowing have a positive effect on seed germination and seedling vigour in Hypericum perforatum L.